2005
DOI: 10.1002/cjg2.637
|View full text |Cite
|
Sign up to set email alerts
|

Apatite Fission Track Evidence for the Thermal History of the Liupanshan Basin

Abstract: The study of apatite fission track suggests that the early Cretaceous deposits in the Liupanshan basin were subjected to two burial heating events. The first heating event occurred during Cretaceous time and reached the maximum temperature prior to the end of Cretaceous. The second one occurred during Eocene‐Late Miocene and reached the maximum temperature at about 8MaB.P. The first maximum burial temperature is higher than the second one. The Cretaceous Naijiahe and Madongshan Formations have lain in the “oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…It is formed by the Haiyuan fault, Tianjingshan fault, and Yantongshan fault from south to north. Among them, the Haiyuan fault is the main fault which underwent different tectonic deformations, i.e., from extrusion by thrusting that began from approximately 8-10 Ma to a sinistral strike-slip motion at 5.4 Ma (Zheng et al, 2005(Zheng et al, , 2006Wang et al, 2013aWang et al, , 2014. The maximum strike-slip displacement was 14 km which was absorbed by the fold deformation and thrust fault located at the end portion of the fault IGCEA et al, 1990;Zhang et al, 1991;Burchfiel et al, 1991).…”
Section: Regional Tectonic Environment and Geometric Distribution Of mentioning
confidence: 98%
“…It is formed by the Haiyuan fault, Tianjingshan fault, and Yantongshan fault from south to north. Among them, the Haiyuan fault is the main fault which underwent different tectonic deformations, i.e., from extrusion by thrusting that began from approximately 8-10 Ma to a sinistral strike-slip motion at 5.4 Ma (Zheng et al, 2005(Zheng et al, , 2006Wang et al, 2013aWang et al, , 2014. The maximum strike-slip displacement was 14 km which was absorbed by the fold deformation and thrust fault located at the end portion of the fault IGCEA et al, 1990;Zhang et al, 1991;Burchfiel et al, 1991).…”
Section: Regional Tectonic Environment and Geometric Distribution Of mentioning
confidence: 98%
“…The fission track ages and magnetostratigraphy data in the west of the Ordos Basin (including the Liupanshan Basin) also indicated the rapid uplift at around 8 Ma (Zhen, 2005;Li, 2007). The Sikouzi anticline in the Liupanshan structure belt consists of the Cretaceous as the core, with parallel unconformity contact with the Neogene, the wings of the anticline.…”
Section: Stage Of Structural Reverse Of the East And West (Late Miocementioning
confidence: 92%
“…Apatite fission track age of the sample taken from the Cretaceous near the Liupanshan fracture belts is 7.5±1.8 Ma, shown by a single peak in the age spectrum, and is consistent with the ages presented by Zhen Dewen in 2005. Zhen's fission track modeling showed that the sample was at the maximum depth, suffered total annealing with the temperature higher than 110 at 8 Ma and then experienced two uplift-cooling events at 8 Ma and 4-2 Ma (Zhen, 2005). Compared with previous stages, the east and south of the Ordos Basin widely deposited red clay sediments of the late Miocene to Pliocene, which overlay on the lower Cretaceous, Anding Formation, Zhiluo Formation of the middle Jurassic, Yan'an Formation of the early-mid Jurassic and Yanchang Formation of the late Triassic (successively from the west to east).…”
Section: Stage Of Structural Reverse Of the East And West (Late Miocementioning
confidence: 99%
“…Recently, it has been emphasized that the critical tectonic event largely controlled the dynamic evolution and the multiple resources well-coexistence of a sedimentary basin [9 -15] . Therefore, the tectonic-event chronology of the dynamic-regime transition in relation to the multi-resources coexistence is becoming an important frontier for the tectonic research and resources exploration in the OB [16][17][18][19][20][21][22][23] .…”
Section: Based On the Analysis Of Apatite And Zircon Fission Track (Fmentioning
confidence: 99%